Study of degradation kinetics of chlorinated phenolic compounds catalyzed by soybean peroxidase. - Cunha, Alexandre Santuchi da (2022)
Soybean peroxidase is a Fe(III)-heme enzyme that can be extracted from soybean seed hulls and has the potential to catalyze the oxidation of some substrates in the presence of hydrogen peroxide. In this research, the degradation of 2,4,6-trichlorophenol, triclosan, and bisphenol-A catalyzed by soybean peroxidase is studied. These substrates are potential pollutants in many industrial and urban effluents, and the assimilation of these substances in large quantities can cause serious health problems. However, the products of their degradation usually show less toxicity than the reagents, being in this case a promising and environmentally friendly industrial effluent remediation method. The main objective of this work is to understand enzymatic degradation kinetics through modeling and simulation performed in MATLAB R2015a, and experiments carried out in a Syrris 250 L microreactor and in batch. Soybean peroxidase was extracted and purified from the soybean seed hulls, to be used in degradation reactions as well as the commercial horseradish peroxidase enzyme. The reaction products were analyzed and quantified through HPLC-UV, and toxicological tests on the reaction mixture both before and after the reaction were also carried out. Different assumptions for the kinetic model were evaluated, and the simulations were compared to experimental data. The results showed the potential of the soybean peroxidase enzyme in degrading chlorinated phenolic components even in a reaction medium with more than one substrate, and that the modified bi-bi ping-pong model can satisfactorily represent the experimental data set. Therefore, a better comprehension of the reaction mechanism can be achieved, contributing to a more accurate reactor project and process simulation of enzymatic reactions.